Perception of users of electronic bulletin board [a case study]. - Choong, Li Yee. (2008)
This study examines users’ perceptions of electronic bulletin boards as effective means of transacting used items. Sellers’ overall transaction experience was found less favourable, compared to buyers'. Also, the importance attributes advanced by the survey and their realisation posterior to an actual transaction were positively associated with users’ satisfaction levels.